2009
DOI: 10.1179/135100009x392421
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofPiper betleon plasma antioxidant status and lipid profile against D-galactosamine-induced hepatitis in rats

Abstract: Betle leaf chewing is an old traditional practice in India and other countries of East Asia. We have investigated the antioxidant and antihyperlipidaemic potential of an alcoholic leaf-extract of Piper betle against D-galactosamine (D-GalN; 400 mg/kg body weight, i.p. single dose) intoxication in male albino Wistar rats. Rats were treated with leaf-extract (200 mg/kg body weight) by intragastric intubations daily for 20 days. The animals were divided randomly into five groups of six animals each as control, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Therefore the decreased HDL levels in D-GalN/LPS-induced rats might be due to the reduced activities of LPL and LCAT [44] . Numerous studies have already reported the increased levels of LDL, VLDL and concomitant reduction in the HDL values during GalN/LPS induced liver injury [2,[47][48][49] . Our present findings clearly match with the above findings.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the decreased HDL levels in D-GalN/LPS-induced rats might be due to the reduced activities of LPL and LCAT [44] . Numerous studies have already reported the increased levels of LDL, VLDL and concomitant reduction in the HDL values during GalN/LPS induced liver injury [2,[47][48][49] . Our present findings clearly match with the above findings.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Another recent study revealed unaltered levels of serum ascorbic and Vitamin E in experimental rats administered with betel leaf extract and challenged with hepatotoxic substance. [9] Similar methods were used in our study although no drug interventions were made to the study subjects. In our study subjects were divided into two groups based on the use of betel leaf in their quid chewing habit.…”
Section: Discussionmentioning
confidence: 99%
“…Many environmental toxins cause liver injury to humans; despite new advances in hepatology, treatment of liver disease does not resolve the problems caused by these toxins. Furthermore, despite considerable progress in treatment of liver disease by oral hepatoprotective agents, the search for newer drugs continues due to the limitations of existing synthetic drugs (Pushpavalli et al, 2009). Therefore, there has been considerable interest in the role of complementary and alternative medicines for treatment of liver diseases.…”
Section: Introductionmentioning
confidence: 99%